Pelatihan Pembuatan Yoghurt Dalam Meningkatkan Pengetahuan dan Motivasi Bisnis Pada Ibu-ibu Rumah Tangga - Oom Komala; Sri Wiedarti (Sasambo: Jurnal Abdimas (Journal of Community Service), 2021)
The purpose of this service program is  provide information and assistance in making yogurt for housewives and provide information about the benefits of yogurt when consumedas well as for business purposes.  This activity was carried out on 10 cadres, Partners of the household industry community group of Perum Dramaga Pratama Rt 06, Cibadak Village, Ciampea District, Bogor Regency. The training method of making yogurt by means of a starter is added to milk and fermentated at 37oC  by the cadres. The evaluation of making yogurt is carried out after 2 days of training to wait for the fermentation process that occurs on the milk base and to determine the success of the program, and after 1 month of implementation to find out the increase in knowledge of the cadres. The results of this activity indicate that the cadre of housewives can make yogurt from milk with a variety of flavors. This training activity is in accordance with the needs of the community, with a relatively sufficient program implementation time according to the needs. Conclusion there is an increase in the knowledge and skills of housewives in Cibadak Village, Sukamakmur District, Bogor Regency in making yogurt 80%. This activity is an achievement for the cadres to increase the skills of a family business venture 20%. Tujuan dari program pengabdian ini adalah untuk memberikan informasi dan pendampingan dalam pembuatan yogurt untuk ibu rumah tangga serta memberikan informasi tentang manfaat yogurt saat dikonsumsi serta untuk tujuan bisnis. Kegiatan ini dilakukan pada 10 kader, Mitra Kelompok masyarakat industri rumah tangga Perum dramaga Pratama Rt 06, Desa Cibadak, Kecamatan Ciampea, Kabupaten Bogor. Metode pelatihan membuat yogurt  dengan cara starter ditambahkan ke susu untuk difermentasi oleh para kader. Evaluasi pembuatan yogurt dilakukan setelah 2 hari pelatihan untuk menunggu proses fermentasi yang terjadi pada basis susu dan untuk mengetahui keberhasilan program, serta setelah 1 bulan pelaksanaan untuk mengetahui peningkatan pengetahuan para kader. Hasil  kegiatan ini menunjukkan bahwa kader ibu rumah tangga dapat membuat yogurt dari susu dengan berbagai macam rasa. Kegiatan pelatihan ini sesuai dengan kebutuhan masyarakat, dengan waktu pelaksanaan program yang relatif cukup sesuai dengan kebutuhan. Sebagian kader telah mampu mengembangkannya untuk bisnis keluarga. Kesimpulan adanya peningkatan pengetahuan dan ketrampilan Ibu-ibu rumah tangga di Desa Cibadak Kecamatan Ciampea, kabupaten Bogor dalam membuat yoghurt 80 %. Kegiatan ini merupakan prestasi bagi para kader dapat meningkatkan ketrampilan usaha bisnis keluarga20%.AbstractThe purpose of this service program is  provide information and assistance in making yogurt for housewives and provide information about the benefits of yogurt when consumedas well as for business purposes.  This activity was carried out on 10 cadres, Partners of the household industry community group of Perum Dramaga Pratama Rt 06, Cibadak Village, Ciampea District, Bogor Regency. The training method of making yogurt by means of a starter is added to milk and fermentated at 37oC  by the cadres. The evaluation of making yogurt is carried out after 2 days of training to wait for the fermentation process that occurs on the milk base and to determine the success of the program, and after 1 month of implementation to find out the increase in knowledge of the cadres. The results of this activity indicate that the cadre of housewives can make yogurt from milk with a variety of flavors. This training activity is in accordance with the needs of the community, with a relatively sufficient program implementation time according to the needs. Conclusion there is an increase in the knowledge and skills of housewives in Cibadak Village, Sukamakmur District, Bogor Regency in making yogurt 80%. This activity is an achievement for the cadres to increase the skills of a family business venture 20%.